Murder in the Marketplace - Victoria Biagi; Alexander Cardazzi; Zachary Porreca (Global Labor Organization (GLO), 2025)
Violence is often viewed as an intrinsic feature of illicit markets, driven by competition, disputes, and predation. We argue that the connection between violence and markets is not exclusive to illicit markets and that in the absence of strong institutions these factors exist ubiquitously. Using an estimator of spatial concentration, we document the empirical relationship between violence and markets in the 14th century. We then employ a large language model to analyze the coroner's accounts of the era's homicides, finding that many of these incidents were driven by avoidable escalations of business-related disputes. Employing a novel difference-in-differences estimator for spatial concentration, we proceed to causally identify the impacts of the introduction of London's first professional police force in the 19th century on this concentration. We find that the police force's introduction led to a 54% reduction in the degree of concentration of violence around marketplaces. Our findings suggest that it is not the nature of the commodities being sold in illicit markets that drives violence, but is rather the absence of formal institutions of enforcement and dispute resolution.
Keywords: K42; N93; R12; C21; K40; N90; 330; marketplace violence; medieval violence; spatial concentration; local large language model